2008
DOI: 10.1111/j.1460-9568.2008.06378.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended secondhand tobacco smoke exposure induces plasticity in nucleus tractus solitarius second‐order lung afferent neurons in young guinea pigs

Abstract: Infants and young children experiencing extended exposure to secondhand smoke (SHS) have an increased occurrence of asthma, as well as increased cough, wheeze, mucus production and airway hyper-reactivity. Plasticity in lung reflex pathways has been implicated in causing these symptoms, as have changes in substance P-related mechanisms. Using whole-cell voltage-clamp recordings and immunohistochemistry in brainstem slices containing anatomically identified second-order lung afferent nucleus tractus solitarius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…Another possible contributing factor to the differences we report may be due to species variations that are independent of the ability to hibernate. However, the following two facts support the view that the major contributor to the differences we saw in this study arose because the hamster is a hibernator and the rat is not: (1) the amplitudes of TS-evoked evoked EPSCs in the NTS at 33°C are similar between rats, guinea pigs, and rhesus monkeys (all non-hibernators) while evoked EPSCs in the hamsters were significantly larger (Sekizawa et al 2008; Sekizawa et al 2010b); and (2) neurons in the medial septum-diagonal band complex of the Yakutian ground squirrel ( Cittelus undulatus ), a hibernating species, have firing rates approximately twice that of corresponding neurons in the guinea pig, and these ground squirrel neurons have been postulated to actively participate in terminating a hibernation bout to ensure full arousal (Belousov et al 1990). Our study plus that of Belousov, et al (1990) indicate that electrical excitability is enhanced in at least two subcortical neural populations in hibernating species.…”
Section: Discussionsupporting
confidence: 76%
“…Another possible contributing factor to the differences we report may be due to species variations that are independent of the ability to hibernate. However, the following two facts support the view that the major contributor to the differences we saw in this study arose because the hamster is a hibernator and the rat is not: (1) the amplitudes of TS-evoked evoked EPSCs in the NTS at 33°C are similar between rats, guinea pigs, and rhesus monkeys (all non-hibernators) while evoked EPSCs in the hamsters were significantly larger (Sekizawa et al 2008; Sekizawa et al 2010b); and (2) neurons in the medial septum-diagonal band complex of the Yakutian ground squirrel ( Cittelus undulatus ), a hibernating species, have firing rates approximately twice that of corresponding neurons in the guinea pig, and these ground squirrel neurons have been postulated to actively participate in terminating a hibernation bout to ensure full arousal (Belousov et al 1990). Our study plus that of Belousov, et al (1990) indicate that electrical excitability is enhanced in at least two subcortical neural populations in hibernating species.…”
Section: Discussionsupporting
confidence: 76%
“…As a nicotinic acetylcholine receptor agonist, nicotine preempts normal cholinergic signals that are critical to the control of neuronal cell replication and differentiation, to the formation of axons and synapses, and to the development of neural circuits. A comparison of nicotine alone vs. tobacco smoke exposure in a variety of models shows similar effects on neurogenesis (Bruijnzeel et al, 2011; Gospe et al, 1996; Slotkin, 2004), oxidative stress (Lobo Torres et al, 2012; Qiao et al, 2005), neural plasticity (Heath and Picciotto, 2009; Sekizawa et al, 2008; Shingo and Kito, 2005), and on indices of cholinergic function, synaptic signaling, and neural cell differentiation into specific neurotransmitter phenotypes (Slotkin, 2004; Slotkin et al, 2000, 2001, 2002, 2006a, b). …”
Section: Introductionmentioning
confidence: 99%
“…However, given the advent of nicotine replacement products for smoking cessation, as well as alternative nicotine delivery devices, it becomes important to distinguish whether the thousands of other components of tobacco smoke also play a role in adverse neurodevelopmental outcomes. A number of animal studies have identified effects of cigarette smoke that, in general, resemble those of nicotine at the biochemical, structural and functional levels (Bruijnzeel et al 2011; Fuller et al 2012; Golub et al 2007; Gospe et al 2009; Lobo Torres et al 2012; Sekizawa et al 2008; Slotkin et al 2006a, b). Nevertheless, these exposure models simply reinforce the resemblance between smoke exposure and the effects of nicotine, rather than distinguishing between them.…”
Section: Introductionmentioning
confidence: 99%